A Transformational Pedagogical Approach to Religious Education in a Multicultural Environment - An’im In ‘Amal Aufa; Hasan Baharun (JURNAL ISLAM NUSANTARA, 2025)
In an increasingly multicultural society, education faces the challenge of fostering not only intellectual competence but also ethical awareness, empathy, and moral responsibility among students. This study aims to explore how transformative religious pedagogy can foster ethical awareness in a diverse student population. Using a qualitative case study design, data were collected through in-depth interviews with faculty and student leaders, classroom observations, and analysis of institutional documents. The research findings reveal three key mechanisms: dialogic faith, which fosters reflective ethical transformation; reflective learning, which nurtures moral awareness through discussion, case analysis, and guided contemplation; and structured multicultural encounters, which strengthen compassionate identity and social responsibility. This study contributes a practical and conceptual model that integrates dialogic, reflective, and intercultural pedagogical approaches in religious education. The implications suggest that educators should implement structured opportunities for dialogue, reflection, and intercultural engagement to foster holistic moral development, bridging theoretical knowledge with ethical practice across diverse educational settings.